Women and literature in Britain 1800 - 1900 (Cambridge Univ. Press, 2001)
"These new essays by leading scholars explore nineteenth-century women's writing across a spectrum of genres. The book's focus is on women's role in and access to literary culture in the broadest sense, as consumers and interpreters as well as practitioners of that culture. Individual chapters consider women as journalists, editors, translators, scholars, actresses, playwrights, autobiographers, biographers, writers for children and religious writers as well as novelists and poets. A unique chronology offers a woman-centered perspective on literary and historical events and there is a guide to further reading."--BOOK JACKET.